The roles of conflict management and psychological empowerment in virtual teams - Biswas, Baidyanath (My University, 2023)
Purpose: This paper aims to determine the impact of perceived virtuality on team dynamics and outcomes by adopting the Input-Mediators-Outcome (IMO) framework. Further, it also investigates the mediating role of team processes and emergent states. Design/Methodology/ Approach: The authors collected survey data from 315 individuals working in virtual teams (VTs) in the information technology sector in India using both offline and online questionnaires. They performed the analysis using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings: The authors investigated two sets of hypotheses - both direct and indirect (or mediation interactions). Results show that psychological empowerment and conflict management are significant in managing VTs. Also, perceived virtuality impacts team outcomes, i.e., perceived team performance, team satisfaction and subjective well-being. Practical Implications: Findings from this study will aid in assessing the consequences of virtual teamwork at both individual and organisational levels, such as guiding the design and sustainability of VT arrangements, achieving higher productivity in VTs, and designing effective and interactive solutions in the virtual space. Theoretical Implications: The study examined the interplay between behavioural team processes (such as conflict management) and emergent states (such as psychological empowerment). The study also theorises and empirically tests the relationships between perceived virtuality and team outcomes (i.e., both affective and effectiveness). It may serve as a guide to understanding team dynamics in VTs better. Originality/ Value: This exploratory study attempts to enhance the current understanding of the research and practice of VTs within a developing economy.
Keywords: Virtual Teams; Input-Mediator-Outcome (IMO) framework; PLS-SEM; Perceived Virtuality; Psychological Empowerment; Conflict Management; Subjective Well-being; Digital Engagement; Digital Humanities; Organisation design, development, theory, behaviour